Manajemen Pengelolaan Situs Geologi Batu Angus dalam Mendukung Pulau Ternate Menuju Geopark Island di Indonesia - Damiasih, Damiasih; Hardi, Nurul Jannah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Batu Angus Geological Site is one of the tourist attractions that can support Ternate Island towards Geopark Island in Indonesia. Although the attraction of this tourist attraction is very potential, it is not yet popular and the visit of foreign and domestic tourists to the location of these attractions is also still not optimal. The objectives of this study are (1) to determine the existence of angus geological sites on Ternate Island, (2) to describe the management of angus geological sites on Ternate Island, and (3) to develop a management strategy for angus geological sites. The method used in this research is descriptive qualitative method where data is obtained through interviews, field observations, documentation, and literature studies. Sampling in this study was carried out using purposive sampling method. The results of this study, namely (1) The Angus Rock Area of Ternate Island has been identified and catalogued by IAGI (Indonesian Geologists Association) North Maluku together with the Ternate City Bappelitbangda Office and the Ternate City Tourism Office, (2) The Angus Rock geological site is very good, but still lacks facilities and infrastructure and lacks Human Resources (HR), the government and the surrounding community need to work together to make the Angus rock geological site into one of the tourist attractions that can support Ternate Island towards a geopark island in Indonesia. (3) The strategy used to improve the management of angus stone geological site in supporting Ternate Island towards Geopark Island in Indonesia by using strength-opportunity strategy, weakness-opportunity strategy, strength-threat strategy, and weakness-threat strategy. The four strategies can make the angus stone geological site better. By applying the right strategies, it can improve the management of Batu Angus geological site on Ternate Island.